Microstrip antenna for television and radio receiver - Fammy Faisal, Rasat (Universiti Malaysia Sarawak, (UNIMAS), 2004)
This project is to determine whether the single rectangular microstrip patch antenna is capable to do its tasks as a TV and radio-receiving antenna. Microwave Office 2001 version 3.22 simulation software was used to generate the Smith Chart, VSWR, S11 Magnitude and Impedance Chart to determine the performance and efficiency of the antenna that was being design. All the results obtained from all the experiments are the tabulated in a tabular form.